Pengaruh Account Representative (AR) dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus pada KPP Pratama Bandar Lampung I) - Wely Erike; Syamsu Rizal (Jurnal EMT KITA, 2023)
This study aims to examine the impact of Account Representative (AR) and Tax Understanding on Taxpayer Compliance (WPOP) with KPP Pratama Bandar Lampung I. The research methodology used is quantified using the Slovin algorithm to calculate the sample number of 100 KPP taxpayers. Pratama Bandar Lampung I. Samples were taken using purposeful sampling technique. Collected data were analyzed using different linear regression methods. The results show that the service quality of the account representative (AR) and the taxpayer's tax knowledge have a significant influence on the taxpayer's tax compliance level. Therefore, it can be concluded that the better the service provided by the Account Manager and the higher the Taxpayer's level of tax knowledge, the better the Taxpayer will fulfill his or her tax obligations. This study makes an important contribution to KPP Pratama Bandar Lampung I by increasing the efficiency of services and the implementation of tax policies. It is hoped that the results of this study can become a benchmark and guide for stakeholders in optimizing efforts to increase overall taxpayer compliance.